PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK PSIKODRAMA UNTUK MENGURANGI TOXIC FRIENDSHIP SISWA SMAN DI PEKANBARU - Putri Yuningsi; Non Syafriafdi; Dian Oktary (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the increasing prevalence of toxic friendship behavior among senior high school students. The study aimed to examine the effectiveness of group guidance services employing psychodrama techniques in reducing students’ toxic friendship behavior. A quantitative approach with an experimental method was applied using a One Group Pretest–Posttest design.Data were analyzed using descriptive statistical techniques, while the effectiveness of the intervention was tested using the Wilcoxon signed-rank test and the N-Gain analysis. The results revealed an N-Gain score of 0.62, indicating a moderate level of effectiveness. These findings suggest that group guidance services integrated with psychodrama techniques are effective in reducing toxic friendship behavior among senior high school students.